Hubungan Antara Kualitas Tidur Dengan Performa Pemain Bola Voli Putra - Dandi Inzaghi, Jonet; Septianingrum, Kartika; Ali Putra, Army Al Islami (S&Co Publishing, 2025)
The purpose of this study is to determine whether there is a relationship between sleep quality and the performance of male volleyball players. This study will be conducted at the IBVOS Volleyball Club, Ngawi District. This research approach will use a quantitative descriptive approach to obtain a comprehensive understanding of the relationship between sleep quality and performance. The design of this study uses correlational research where correlational research aims to determine the relationship between two or more variables. The sample that will be the subject of the study is the IBVOS A volleyball club players in Ngawi Regency, totaling 25 players. To collect data on sleep quality, researchers will use the Pittsburgh Sleep Quality Index (PSQI) questionnaire. The VO2 Max test uses the MFT Test. Correlation analysis using the correlation coefficient test aims to determine the degree of relationship between variable X (sleep quality) and variable Y (performance). Based on the formulation of the problem, from the results of this study it can be concluded that there is a relationship between sleep quality and the performance of IBVOS Club volleyball players with a significance value of 0.017 <0.05, and the calculated R value is known that the calculated R value for the relationship between sleep quality and volleyball player performance is 0.479> R table 0.396